IMPLEMENTASI METODE ANALYTICAL HIERARCY PROCESS (AHP) UNTUK ANALISIS FAKTOR KEAMANAN LAUT INDONESIA - Moh Badri Tamam; Hozairi Hozairi (Jurnal Aplikasi Teknologi Informasi dan Manajemen (JATIM), 2020)
Indonesia is an island nation consisting of 17,504 islands and has 81,290 kilometers of coast. Indonesia has 12 (twelve) law enforcement agencies at sea, the twelve institutions have carried out their duties and functions, but have not synergized, so that sea security is not only influenced by the number of institutions, but is influenced by many factors, namely: Political and legal factors, economic factors, security and security factors, socio-cultural factors, environmental factors, technological factors, so that Indonesia needs a marine security model to determine the factors that most influence Indonesian sea security using the Analytical Hierarchy Process (AHP Method). For program calculations we use web programming. Research results: [1] Defense and security = 0.40, [2] Politics and law = 0.22, [3] Technology = 0.14, [4] Environment = 0.09, [5] Economics = 0, 06, [6] Social culture = 0.06. The sub-factor criteria that most influence each factor are as follows: [1] Defense and security = Expenditures (0.28), [2] Politics and law = Division of zones of sea areas (0.37), [3] Technology = Cyber ​​Attack (0.52), [4] Environment = Geographical condition of the disaster zone (0.44), nn [5] Economy = Indonesian economic growth (0.30), [6] Social culture = Maritime cultural awareness (0 , 44). So the factors and sub-factors that most influence on Indonesia's sea security are defense and security factors with the national defense expenditure expenditure sub-factor.